Changes in health worker knowledge and motivation in the context of a quality improvement programme in Ethiopia. Issue 10 (10th August 2021) - Quaife, Matthew; Estafinos, Abiy Seifu; Keraga, Dorka Woldesenbet; Lohmann, Julia; Hill, Zelee; Kiflie, Abiyou; Marchant, Tanya; Borghi, Josephine; Schellenberg, Joanna
Abstract: A knowledgeable and motivated workforce is critical for health systems to provide high-quality services. Many low- and middle-income countries face shortages in human resources and low health worker motivation but are also home to a burgeoning number of quality improvement (QI) programmes. This study evaluates whether and how motivation and clinical knowledge in three cadres of health workers changed in the context of a QI programme for maternal and newborn health in Ethiopia. This mixed-methods study used a pre–post comparison group design with matched comparison areas. We interviewed 395 health workers at baseline in April 2018 and 404 at endline in June 2019 from seven districts (woredas) with QI and seven comparison woredas. Three cadres were interviewed: health extension workers, facility-based skilled midlevel maternal and newborn care providers, and non-patient-facing staff. A qualitative component sought to triangulate and further elucidate quantitative findings using in-depth interviews with 22 health workers. Motivation was assessed quantitatively, exploratory factor analysis was used to categorize motivation dimensions, and regression-based difference-in-difference analyses were conducted. Knowledge was assessed through a clinical vignette. Qualitative data were analysed in a deductive process based on a framework derived from quantitative results. Although knowledge of the QI programme was high (79%) among participants from QI woreda at endline, participation in QI teams was lower (56%). There was strong evidence that health worker knowledge increased more in areas with QI than comparison areas. Three motivation dimensions emerged from the data: (1) 'helping others', (2) 'pride and satisfaction' and (3) 'external recognition and support'. We found strong evidence that motivation across these factors improved in both QI and comparison areas, with weak evidence of greater increases in comparison areas. Qualitative data suggested the QI programme may have improved motivation by allowing staff to provide better care. This study suggests that although QI programmes can increase health worker knowledge, there may be little effect on motivation. Programme evaluations should measure a wide range of outcomes to fully understand their impact.